Theory and method in higher education research. Vol. 1 - Huisman, Jeroen; Tight, Malcolm (Bingley, U.K. : Emerald, 2015)
Higher education research is a developing field internationally, which is attracting more and more researchers from a great variety of disciplinary backgrounds within and beyond higher education institutions. As such, it is an arena within which a wide range of theories, methods and methodologies is being applied. Theory and method in higher education research I contains contemporary contributions to international debates regarding the application and development of theory and methodology in researching higher education.
The use of institutional theory in higher education research / Yuzhuo Cai, Yohannes Mehari -- The role of political and policy studies in higher education policy research / Andrew Gunn -- Evaluative research in higher education policy analysis / Murray Saunders, Cristina Sin, Steven Dempster -- Event history analysis : a primer for higher education researchers / Austin Lacy -- Efficiency in higher education : requirements, theory, methods and decision areas / Matthias Klumpp -- Three methods, four different outcomes! How to test the reliability and validity of a graduate survey competence scale / Mareike Landmann ... [et al.] -- The change laboratory in higher education : research-intervention using activity theory / Brett Bligh, Michelle Flood -- What works? A critique of appreciative inquiry as a research method/ology / Lynn Clouder, Virginia King -- Images in research on teaching and learning in higher education / Erika Lo<U+0308>fstro<U+0308>m ... [et al.] -- Exploring doctoral examiner judgements through the lenses of Habermas and epistemic cognition / Neville Clement ... [et al.] -- Theorising academic development as an academic discipline? Exploring academic developers' ways of knowing, theorising and use of methods / Megan Y.C.A. Kek, Sara Hammer -- Theorising inequality : two-dimensional participatory justice and higher education research / Andrew Morrison -- A normative framework or an emerging theory? The capability approach in higher education research / Ana Sofia Ribeiro -- Engineering phenomenography / Peter Gibbings, John Lidstone, Christine Bruce -- The narrative approach in higher education research / Anto<U+0301>nio Magalha<U+0303>es, Ame<U+0301>lia Veiga.
Print version record
Keywords: Education -- Higher; Higher & further education, tertiary education; Education, Higher -- Research; Education, Higher -- Research -- Methodology